1994
DOI: 10.1016/0014-5793(94)01130-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activation of intercellular adhesion molecule 1 (ICAM‐1) by TNF‐α and IFN‐γ is mediated by p65/p50 and p65/c‐Rel and interferon‐responsive factor Statlα (p91) that can be activated by both IFN‐γ and IFN‐α

Abstract: Human ICAM-expression is up-regulated by IFN-r and TNF-a and synergistically increased by a combination of both. Transient expression of ICAM-l/luciferase constructs led to definition of the regulatory regions mediating the cytokine response and showed that both are necessary for synergism. Immunochemical electromobility shift assays identified the TNF-o-dependent complexes that bound to the NF-rcB like sequence at -187 as p65/p50 and p65/c-Rel. The interferon responsive region at -75 was bound by a Statla (p9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 46 publications
4
75
0
2
Order By: Relevance
“…We have observed that both GAS and ISRE do not compete with pI␥RE even at a 1000-fold excess in our experiments using HK cell lysates. Our results are in agreement with the report that shows GBP⅐GAS does not compete with the ICAM-1 IFN␥RE in airway epithelial cells (20) and are in contrast to those obtained by others in MeL JuSo cells (42).…”
Section: Icam-1 Gene Induction By Ifn␥ Via a Distinct Stat Complexsupporting
confidence: 94%
“…We have observed that both GAS and ISRE do not compete with pI␥RE even at a 1000-fold excess in our experiments using HK cell lysates. Our results are in agreement with the report that shows GBP⅐GAS does not compete with the ICAM-1 IFN␥RE in airway epithelial cells (20) and are in contrast to those obtained by others in MeL JuSo cells (42).…”
Section: Icam-1 Gene Induction By Ifn␥ Via a Distinct Stat Complexsupporting
confidence: 94%
“…It has been shown that priming with IFN-g augments NF-kB activation and the expression of NF-kB target genes induced by ligands of TLRs, including LPS in macrophages (47). The molecular mechanism underlying the augmentation of NF-kB activation by IFN-g pretreatment is not well understood, although the combined presence of the binding sites of STAT1, which is an IFN-g-inducible transcriptional activator, and the NF-kB binding sites in the promoter region of many NF-kB target genes has been demonstrated (47)(48)(49). We also showed that IFN-g increases the amount of LUBAC and LPSmediated NF-kB activation in BMDMs.…”
Section: Ifn-a Increased the Amount Of Lubac And Ameliorated Dermatitmentioning
confidence: 99%
“…36 Subconfluent cells were transfected with Effectene (Qiagen) containing a construct of firefly luciferase ligated to an NF B-sensitive promotor of the human ICAM-1 gene (277-ICAM-1) 37 and a control construct of renilla luciferase ligated to an NF B-insensitive tyrosin-kinase promotor, 24 h later, cells were stimulated with TNF␣ (100 ng/ml). NF B decoy ODN (2 g/well) containing liposomes were added either at stimulation (0 h) or 24 h before (-24 h).…”
Section: Cell Culture Experimentsmentioning
confidence: 99%